2015
DOI: 10.1149/2.0231503jss
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pb Doping on Hole Transport Properties and Thin-Film Transistor Characteristics of SnO Thin Films

Abstract: Effects of Pb doping on the microstructural, optical, and hole transport properties of Sn 1−xf Pb xf O films fabricated by pulsed laser deposition were investigated. It was found that Pb was not solved in bulk ceramic samples, while solved up to x f = 0.035 in the thin films. The Pb doping enlarged the optical bandgap, decreased the hole concentration, and reduced the Hall mobility (μ Hall , from 1.95 to 0.68 cm 2 V −1 s −1 up to x f = 0.035) as x f increased. The field-effect mobility in thin-film transistors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Fabrication of SnO thin films has been extensively evaluated using a series of methods, including physical vapor deposition (PVD) routes, such as PLD, EB, RFMS, and DCMS using Sn, SnO, and SnO 2 targets on both rigid and flexible substrates. The Hall mobility and carrier (hole) concentrations, along with the deposition conditions are listed in Table 3 for relatively recent studies.…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Fabrication of SnO thin films has been extensively evaluated using a series of methods, including physical vapor deposition (PVD) routes, such as PLD, EB, RFMS, and DCMS using Sn, SnO, and SnO 2 targets on both rigid and flexible substrates. The Hall mobility and carrier (hole) concentrations, along with the deposition conditions are listed in Table 3 for relatively recent studies.…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Ogo et al reported an activation energy of 45 meV in epitaxial SnO thin films, which suggests an acceptor energy level90 meV above the VBM [8]. Poly-crystalline thin films show slightly higher activation energy (60 meV) compared to epitaxial SnO thin films [58]. Polycrystalline thin films also show increased barrier potentials at the grain boundaries which cause mobility deterioration in the films [58].…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Poly-crystalline thin films show slightly higher activation energy (60 meV) compared to epitaxial SnO thin films [58]. Polycrystalline thin films also show increased barrier potentials at the grain boundaries which cause mobility deterioration in the films [58]. It has been…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…On the other hand, there are works in the literature that report the introduction of impurities into the SnO structure to improve its physical properties. Among the different mentioned impurities that may produce p‐type SnO thin films are Y, Sb, Cu, Pb, and N . Nitrogen has also been used as an impurity to induce a change in the conduction from n‐type to p‐type in oxides such as ZnO, Ta 2 O 5, and SnO 2.…”
Section: Introductionmentioning
confidence: 99%